2011
DOI: 10.1371/journal.pone.0021884
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Allochthonous Dissolved Organic Carbon in Lakes: A Quantitative Approach

Abstract: Inputs of dissolved organic carbon (DOC) to lakes derived from the surrounding landscape can be stored, mineralized or passed to downstream ecosystems. The balance among these OC fates depends on a suite of physical, chemical, and biological processes within the lake, as well as the degree of recalcintrance of the allochthonous DOC load. The relative importance of these processes has not been well quantified due to the complex nature of lakes, as well as challenges in scaling DOC degradation experiments under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 43 publications
6
112
1
1
Order By: Relevance
“…4) to only about 2000-2200 mm yr −1 at the other two locations in the central and southern part of Amazonia (see Table 5). Similar throughfall flux has also been reported for tropical rainforest in Indonesia (12.6 to 16.4 g C m −2 yr −1 , Fujii et al, 2011) as well as for primary, sub-tropical rainforests in Puerto Rico (13.2 g C m −2 yr −1 , Heartsill-Scalley et al, 2007) and Taiwan (18.9 g C m −2 yr −1 Liu and Sheu, 2003). …”
Section: Doc In Precipitation and Throughfallsupporting
confidence: 82%
“…4) to only about 2000-2200 mm yr −1 at the other two locations in the central and southern part of Amazonia (see Table 5). Similar throughfall flux has also been reported for tropical rainforest in Indonesia (12.6 to 16.4 g C m −2 yr −1 , Fujii et al, 2011) as well as for primary, sub-tropical rainforests in Puerto Rico (13.2 g C m −2 yr −1 , Heartsill-Scalley et al, 2007) and Taiwan (18.9 g C m −2 yr −1 Liu and Sheu, 2003). …”
Section: Doc In Precipitation and Throughfallsupporting
confidence: 82%
“…DOC mineralization rates increase with increasing temperatures, mixed-layer depths, and residence times (Hanson et al 2011). Thus, as DOC concentrations are increased, lakes decrease in volumetrically averaged temperature and stratify more shallowly, and this can depress biological mineralization rates to further increase DOC concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…High DOC concentrations reduce transparency, which can alter the vertical structure of water temperature and lead to shallower surface mixed layers (Kling 1988;Fee et al 1996;Persson and Jones 2008). In turn, water temperature and the depth of the mixed layer can significantly influence ecosystem-scale characteristics, such as the processing rates of carbon (Hanson et al 2011). Many investigators have highlighted long-term changes in lacustrine DOC loading and catchment export (Schindler et al 1996;Striegl et al 2005;Zhang et al 2010).…”
mentioning
confidence: 99%
“…A reduction of phosphorus entering Lake Brates and an estimation of maximum allowable level for some contaminants can greatly reduce the pollution status of the lake. The recorded and high correlative value of total hardness, Mg and Ca hardness, organic matter, suspended solids and other variables such as turbidity, color and the immobilization of physico-chemical and biological elements in the sediments (see An excess supply of organic, mineral, trace and heavy metals with subsequent losses to the aquatic environment can lead to adverse effects on both the ecology and uses of receiving waters as presented in Tables 2 and 3 and substantiated by the findings of Hanson et al (2011) and Gazzaz et al (2012). The process of accelerated enrichment and its impacts, arising from human activities, is termed cultural eutrophication and has been recognized internationally as a significant environmental problem/challenge for a number of decades, particularly since the influential reports and cooperative environmental programmes have been initiated (Vollenweider and Kerekes 1982).…”
Section: Journal Of Environment and Ecologymentioning
confidence: 69%
“…While scientists are still studying the effects of high chemical levels in humans, studies have suggested that toxic chemicals can lead to reproductive problems, cancer and neurological disorders (Hanson et al 2011). People who are most at risk of health problems due to contaminated fish consumption are those with weakened immune systems, including children, pregnant women and the elderly.…”
Section: Journal Of Environment and Ecologymentioning
confidence: 99%